Predicted changes in herd immunity levels against Rift Valley fever virus in livestock following a natural exposure - Gachohi, John M.; Bett, Bernard K. (International Livestock Research Institute, 2014)
Introduction Rift Valley fever virus (RVFV) transmission gets elevated following periods of excessive and persistent rainfall. The average inter-epizootic period in Kenya has been estimated to be 3.6 years (range 1–7 years). It is presumed that herd immunity plays an important role in modifying the length of these intervals given that the risk of an epidemic intensifies when herd immunity is low. The objective of this study was to evaluate the relationship between herd immunity and RVFV transmission dynamics.